Performance and emission trade-off assessment for aero-gas turbine engine - Azami, Muhammad Hanafi; Savill, Mark (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Environmental and performance aspect has emerged as an essential trade-off in the design phase of novel engines. From design’s point of view, not only engine performance requirements, external factors such as cost and environmental issues are all required to be in place. At present, there are myriad works on optimization and trade-off performance and environmental impacts are being done. This work provides a systematic trade-off solution to address the performance and emission for aero-gas turbine engine such as RB211. Four types of fuels namely algae biofuel, Jatropha biofuel, Camelina biofuel, and kerosene fuel are studied. Prior to the trade-off assessment, data from performance analysis using in-house software PYTHIA and emission analysis (in-house software: HEPHAESTUS) are compiled to first identify the necessary parameters needed in each computer tool subsequently. A design of experiment (DoE) using general factorial is used in Minitab software to follow an explorative approach, offering an alternative solution to the practicability in this work. Performance and emission parameter that were studied are thrust specific fuel consumption (TSFC) and nitrous oxides emission indices (EINOx). It was found that the contrasting effects of EINOx and TSFC due to speed factor require a trade-off evaluation. High speed results in reduction in TSFC, but not EINOx.